Cover Image, Volume 171B, Number 3, April 2016. Issue 3 (April 2016) - Green, Tamar; Fierro, Kyle C.; Raman, Mira M.; Saggar, Manish; Sheau, Kristen E.; Reiss, Allan L.
Abstract : The cover image, by Tamar Green et al., is based on the Research Article Surface‐based morphometry reveals distinct cortical thickness and surface area profiles in Williams syndrome, DOI:10.1002/ajmg.b.32422 .